A Response to Nicholas Wolterstorff - Smith, Steven (Christian scholar's review, 2010)
It is an honor to have The Disenchantment of Secular Discourse reviewed by a person and scholar of the stature of Nicholas Wolterstorff – and a relief to see that the review is generally favorable. Wolterstorff presents the principal arguments of the book succinctly and sympathetically and offers some perceptive criticisms. These criticisms prompt me to attempt not a rebuttal, but rather a few clarifications.